1992
DOI: 10.1002/mrd.1080310310
|View full text |Cite
|
Sign up to set email alerts
|

Subzonal insemination with a single spermatozoon using manipulation assisted sperm adhesion onto the ooplasmic membrane in mouse ova

Abstract: A simple and successful method of microinjection of a single spermatozoon under the zona pellucida of a mouse oocyte has been developed. A characteristic of this method is that the tip of the sperm injection needle pierces the zona pellucida without touching the ooplasmic membrane. All the ova (277) used for this series of experiments had normal morphology after the injection procedure. Spermatozoa preincubated in culture medium for capacitation and those treated with ionophore A23187 for induction of acrosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…According to the results, it is thought that -70% (87.5% of 78.0%) of the normalappearing sperm population will fertilize oocytes that will develop into blastocysts. Additionally, our previous experiment (Kobayashi et al, 1992a) has revealed that -70% of mouse oocytes microinjected with a single spermatozoon under the zona pellucida were fertilized and almost one-half of the generated zygotes developed normally into offspring after implantation. Considering our data, it is conceivable that a considerable number of spermatozoa in a population may have the potential to fertilize oocytes and contribute to their further development with the aid of the micromanipulation technique.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…According to the results, it is thought that -70% (87.5% of 78.0%) of the normalappearing sperm population will fertilize oocytes that will develop into blastocysts. Additionally, our previous experiment (Kobayashi et al, 1992a) has revealed that -70% of mouse oocytes microinjected with a single spermatozoon under the zona pellucida were fertilized and almost one-half of the generated zygotes developed normally into offspring after implantation. Considering our data, it is conceivable that a considerable number of spermatozoa in a population may have the potential to fertilize oocytes and contribute to their further development with the aid of the micromanipulation technique.…”
Section: Discussionmentioning
confidence: 98%
“…A droplet of sperm suspension in methyl cellulose was also placed in the same well, and both droplets were covered with mineral oil. The above procedures for gamete preparations were described in detail elsewhere (Kobayashi et al, 1992a).…”
Section: Materials and Methods Preparation Of Oocytes And Spermatozoamentioning
confidence: 99%
See 3 more Smart Citations